2021
DOI: 10.3389/fpsyg.2021.644106
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Depressive Symptoms and Physical Activity Intensity in an Older Adult Population During COVID-19 Lockdown

Abstract: IntroductionThe COVID-19 pandemic led to the implementation of physical–social distancing measures–including self-isolation, home confinement, and quarantine around the world, with psychological consequences such as depression. Older adults are especially likely to develop depressive symptomatology. This study aims to investigate the association between physical activity intensities and sedentary behavior with depression levels among previously active older adults during the COVID-19 lockdown.MethodsA total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 28 publications
(45 reference statements)
5
25
0
3
Order By: Relevance
“…Two study collected measures after the stay-at-home order and during this period physical activity mean score decreased minimally [ 51 ], and depressive symptoms increase as the weeks of isolation go [ 28 ]. Other studies also reported a reduction in self-reported PA [ 26 , 33 , 34 , 37 , 38 , 42 , 43 , 45 , 56 , 57 ] and increase in sedentary behaviour [ 25 , 26 , 34 ]. Individuals who reported larger decrease in MVPA pre to during COVID-19 reported relatively poorer mental health [ 33 ].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Two study collected measures after the stay-at-home order and during this period physical activity mean score decreased minimally [ 51 ], and depressive symptoms increase as the weeks of isolation go [ 28 ]. Other studies also reported a reduction in self-reported PA [ 26 , 33 , 34 , 37 , 38 , 42 , 43 , 45 , 56 , 57 ] and increase in sedentary behaviour [ 25 , 26 , 34 ]. Individuals who reported larger decrease in MVPA pre to during COVID-19 reported relatively poorer mental health [ 33 ].…”
Section: Discussionmentioning
confidence: 95%
“…Participants sufficiently active during covid-19 reported significantly lowe depression and anxiety, and higher life satisfaction. Lage et al 2021 [ 34 ] Cross-sectional, 1123 older adults (mena age 67.68 ± 5.91, 91% female), interviewed by telephone call, Brazil. Depression (GDS-15).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the current scenario is impacting all aspect of our lives, from socio-economic [8,9], health [10], environmental [11], and educational [12] perspectives. In particular, many studies have reported that the pandemic resulted in increased psychiatric disorders such as post-traumatic stress, depressive, and anxiety disorders, as well as grief-related symptoms in adolescents [13][14][15][16] and adults [17,18].…”
Section: Introductionmentioning
confidence: 99%